Big Data Analytics: The New Boundaries of Retail Location Decision Making. (2nd October 2018) - Aversa, Joseph; Doherty, Sean; Hernandez, Tony
Abstract: Over recent years, the rapid growth of big data and associated analytical tools has provided unparalleled opportunities for retailers to enhance their location decision support activities. To date, there is a lack of research that looks at how retail firms are leveraging such innovation in data and technology. Based on an online survey conducted with Canadian retail location decision makers, this article examines the current state and evolution in (1) the type and scale of location decisions that retail firms undertake; (2) the availability and use of technology and geospatial data within the decision-making process; and (3) the range of location research methods that are employed. The findings highlight that there has been a widespread increase in the availability and use of technology and geospatial data within the decision-making process. The range of analytical approaches has also expanded to include methods that work with new data sources, such as social media and mobile device location data. The adoption and development of big data approaches is also challenged, however, by factors such as information hoarding, a lack of understanding and buy-in from senior management, and a lack of skilled analysts who can manage and synthesize the big data.